First branchial cleft sinus with duplicate external auditory canal: A case report - Matthew Jorizzo; Ryan Li (Clinical Case Reports, 2022)
Abstract First branchial cleft cysts are rare congenital abnormalities of the lateral neck. These anomalies can be a source of recurrent infection and require surgical excision as definitive treatment. This case report details the diagnosis and treatment of a first branchial cleft sinus with an associated duplicate external auditory canal.